A physicochemical, thermodynamical, structural and computational evaluation of kynurenic acid/cyclodextrin complexes. (15th September 2021) - Matencio, Adrián; Caldera, Fabrizio; Rubin Pedrazzo, Alberto; Khazaei Monfared, Yousef; K. Dhakar, Nilesh; Trotta, Francesco
Highlights: The interaction of KYNA and several cyclodextrins (CDs) was studied. The modified HPβ-CD showed the strongest complexation constant (KF) The results showed high dependence on pH and temperature. Abstract: In this work, the interaction between Kynurenic acid (KYNA) and several natural and modified cyclodextrins (CDs) is carried out. Among all the CD tested, HPβ-CD showed the strongest complexation constant (KF ), with a value of 270.94 ± 29.80 M −1 . Between natural (α- and β-) CDs, the complex of KYNA with β-CD was the most efficient. The inclusion complex of KYNA with CDs showed a strong influence of pH and temperature. The KF value decreased at high pH values, when the pKa was passed . Moreover, an increase of the temperature caused a decrease in the KF values. The thermodynamic parameters of the complexation (Δ H °, Δ S ° and Δ G °) were studied with negative entropy, enthalpy and spontaneity of the process at 25 °C. Moreover, the inclusion complex was also characterized using FTIR and TGA. Finally, molecular docking calculations provided different interactions and their influence in the complexation constant.